TOP2A as a prognostic biomarker in small cell carcinoma of the esophagus: an integrated bioinformatics and immunohistochemical study - Xiaolei Yin; Xiaopeng Li; Lili Mi; Jiaojiao Hou; Fei Yin (Frontiers in Molecular Biosciences, 2025)
BackgroundSmall cell carcinoma of the esophagus (SCCE) is an infrequent but highly aggressive cancer with a poor prognosis. Given its low incidence, there is a lack of validated biomarkers to guide risk stratification and inform treatment decisions.MethodsWe extracted Differentially expressed genes (DEGs) from the GSE111044 dataset using standard bioinformatics workflows. A network of interacting proteins was assembled to determine hub genes, and TOP2A and CDK1 were selected for immunohistochemical (IHC) validation in 76 SCCE tumor samples. IHC staining scores were analyzed for associations with clinicopathological features. Survival analysis was conducted using Kaplan–Meier estimations and Cox regression modeling to pinpoint independent prognostic factors. To further assess the clinical utility, TOP2A expression was combined with VALSG staging for risk stratification.ResultsA comparison between SCCE and adjacent normal tissues revealed 1,202 DEGs. PPI network analysis highlighted two hub genes, TOP2A and CDK1, which IHC validated in 76 SCCE samples. High TOP2A expression was significantly associated with advanced TNM stage (p = 0.020) and deeper tumor invasion (p = 0.004). Multivariate Cox analysis identified high TOP2A expression (HR = 1.92, 95% CI: 1.30–2.82, p = 0.001) and VALSG stage (HR = 2.20, 95% CI: 1.07–4.50, p = 0.031) as independent predictors of prognosis. Time-dependent ROC analysis indicated that the AUCs for the VALSG stage alone were 0.626, 0.638, and 0.602 at 1-, 2-, and 3-year time intervals, respectively. TOP2A alone yielded slightly higher AUCs of 0.719, 0.632, and 0.676. Notably, the combination of TOP2A and VALSG provided the greatest predictive accuracy, achieving AUCs recorded at 0.721, 0.734, and 0.773 at the respective time points.ConclusionThis study suggests that TOP2A is a novel, independent prognostic biomarker in SCCE. When integrated with the VALSG staging system, TOP2A expression enhances risk stratification and may serve as a useful adjunct in clinical prognostication. These findings support its clinical utility while emphasizing the necessity for future studies to include prospective validation.